STUDI KASUS POLA BENTURAN BANGUNAN PADA SISTEM SATU DERAJAT KEBEBASAN (DOF) (Eternitas: Jurnal Teknik Sipil, 2022)
The linear and nonlinear response of two buildings with one degree of freedom (DOF) respectively vibration period (T) 0.4 second and 0.5 second are becoming the models of this research. The earthquake record of Loma Prieta 1989 is selected and customized with the spectrum response curve Ss = 1.25g and S1 = 0.4g with the medium ground (SD). The spring of building structure modelled as linear and nonlinear spring of Takeda model that has been modified. The important results of this research are: first, the direct addition method is only used to determine time of collision and not adequate to determine seismic separation. Second, the ultimate method or the transform method to calculate elastic deformation multiplied Cd/Ie is only used when the building does not have large inelastic deformation. Third, the pattern transformation of building response after inelastic phase could be significantly and bear the opportunity of both building collision.